Migration measurement of the cemented Lubinus SP II hip stem - a 10-year follow-up using radiostereometric analysis - Sesselmann, Stefan; Hong, Yutong; Schlemmer, Frank; Wiendieck, Kurt; Söder, Stephan; Hussnaetter, Isabell; Müller, Lutz Arne; Forst, Raimund; Wierer, Thomas (Biomedizinische Technik, 2016)
In a previous radiostereometric analysis (RSA) of the Lubinus SP II (Link, Hamburg, Germany), which is one of the most often used cemented hip stems worldwide, our research group detected a very small but statistically significant distal migration of -0.03±0.17 mm 2 years after surgery compared to the postoperative radiograph. Maximum subsidence occurred between 6 and 12 months. The implant appeared to have stabilized after 2 years. The mean value of maximum total point motion (MTPM) was 0.99±0.69 mm, which was detected 2 years after surgery. The purpose of this study was to analyze the migration pattern and to verify the predictive value of short-term RSA of the Lubinus SP II stem after 10 years. After a follow-up of 5 and 10 years, 38 and 27 out of 100 patients remained available for further assessment, respectively. No statistically significant implant translation or rotation was found along or about the axes of the global coordinate system 5 and 10 years after surgery with respect to the postoperative radiograph. Furthermore, the MTPM was stable in both follow-up periods. The results suggest that the Lubinus SP II hip stem is still stable 10 years after surgery, supporting that determining prognosis by short-term RSA follow-up of 2 years could be an appropriate tool for appraisal of implant behavior 10 years after surgery.
EVALuna2:6812